2019
DOI: 10.1074/mcp.ra118.001221
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Mass Spectrometry Strategy for Developing Proteomic Biomarkers: A Case Study of Epithelial Ovarian Cancer

Abstract: Highlights • Rigorous experimental design and data analysis for large-scale SRM studies. • Plasma-based biomarker signature combined with CA125 for ovarian cancer detection. • Broadly applicable strategy for the development of diagnostic biomarker assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…Chang et al provide insights regarding sample size requirements for SRM measurements based on SRM variability in plasma from human ovarian cancer patients, and demonstrate that approximately 50 cases and 50 controls would be required to detect a fold change in a specific protein of 1.2 with 80% power and a 5% type I error rate [ 52 ]. If serum is the focus, these estimates can serve as a starting point for planning pilot studies in serum to evaluate variability for use in full study planning [ 53 ]. Fortunately, tools exist to assist in assessing these study design parameters during the study planning stages, and authors are starting to report information regarding technical and biological variability in addition to fold change, enabling educated parameter estimates for use in calculations [ 52 , 54 , 55 , 56 , 57 ].…”
Section: Experimental Design and Statistical Considerations In Sermentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al provide insights regarding sample size requirements for SRM measurements based on SRM variability in plasma from human ovarian cancer patients, and demonstrate that approximately 50 cases and 50 controls would be required to detect a fold change in a specific protein of 1.2 with 80% power and a 5% type I error rate [ 52 ]. If serum is the focus, these estimates can serve as a starting point for planning pilot studies in serum to evaluate variability for use in full study planning [ 53 ]. Fortunately, tools exist to assist in assessing these study design parameters during the study planning stages, and authors are starting to report information regarding technical and biological variability in addition to fold change, enabling educated parameter estimates for use in calculations [ 52 , 54 , 55 , 56 , 57 ].…”
Section: Experimental Design and Statistical Considerations In Sermentioning
confidence: 99%
“…While it is tempting to take short-cuts and proceed with small numbers or pool specimens due to the time- and resource-intensive nature of proteomics experiments, it has been shown that it is possible to proceed with larger sample sizes with the appropriate use of controls, replication, and statistical analysis tools for quantification and hypothesis testing [ 53 , 58 ]. The pooling of specimens prior to mass analysis without the specimens being labeled should be avoided, as it relies on the assumption of biological averaging and constrains the types of analyses that can be performed [ 59 ].…”
Section: Experimental Design and Statistical Considerations In Sermentioning
confidence: 99%
“…The study reports on a novel strategy for the discovery of tumor-derived proteins using a combination of N-glycoproteomics and PDX models. A similar study was performed by Hüttenhain et al [174]. Genetically engineered ovarian cancer mouse models and control mice samples were used for the selection of N-glycoproteomic biomarker candidates which were quantified by SRM in 124 patient sera with epithelial ovarian cancer and 110 healthy controls.…”
Section: Blood-based Proteomicsmentioning
confidence: 97%
“…Sequential Windowed Acquisition of All Theoretical Fragment Ion Mass Spectra (SWATH-MS) is one of the DIA methods that has been employed to produce highly reproducible and complete quantitative results [1][2][3] . This property of SWATH-MS enables the general application of SWATH-based quantitative proteomics in biological research and clinical biomarker studies [4][5][6] . SWATH-MS data analysis can be accomplished by two strategies, spectral library-based targeted analysis approach and library-free analysis method.…”
Section: Background and Summarymentioning
confidence: 99%